2019
DOI: 10.5194/acp-19-2343-2019
|View full text |Cite
|
Sign up to set email alerts
|

Wintertime secondary organic aerosol formation in Beijing–Tianjin–Hebei (BTH): contributions of HONO sources and heterogeneous reactions

Abstract: Abstract. Organic aerosol (OA) concentrations are simulated over the Beijing–Tianjin–Hebei (BTH) region from 9 to 26 January 2014 using the Weather Research and Forecasting model coupled with chemistry (WRF-CHEM), with the goal of examining the impact of heterogeneous HONO sources on SOA formation and SOA formation from different pathways during wintertime haze days. The model generally shows good performance with respect to simulating air pollutants and organic aerosols against measurements in BTH. Model resu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
62
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 74 publications
4
62
1
Order By: Relevance
“…However, aqueous-phase formation of SOA has also been considered an important pathway during some pollution events in, e.g., Beijing, Shijiazhuang and Baoji Wang et al, 2017;Huang et al, 2019). The formation of less-oxidized oxygenated OA (LO-OOA) and moreoxidized oxygenated OA (MO-OOA) in Baoji seemed to be significantly influenced by aqueous-phase chemistry during the period of low atmospheric oxidative capacity , while in another study Xu et al (2017) suggested that aqueous-phase processing has a dominant impact on MO-OOA formation but that photochemical oxidation is the dominant pathway for LO-OOA formation in Beijing. It is still unclear whether aqueous-phase processing plays a key role in haze development and what the mechanisms are.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, aqueous-phase formation of SOA has also been considered an important pathway during some pollution events in, e.g., Beijing, Shijiazhuang and Baoji Wang et al, 2017;Huang et al, 2019). The formation of less-oxidized oxygenated OA (LO-OOA) and moreoxidized oxygenated OA (MO-OOA) in Baoji seemed to be significantly influenced by aqueous-phase chemistry during the period of low atmospheric oxidative capacity , while in another study Xu et al (2017) suggested that aqueous-phase processing has a dominant impact on MO-OOA formation but that photochemical oxidation is the dominant pathway for LO-OOA formation in Beijing. It is still unclear whether aqueous-phase processing plays a key role in haze development and what the mechanisms are.…”
Section: Introductionmentioning
confidence: 91%
“…Compared to primary aerosol that is relatively well constrained in terms of the emission sources, secondary aerosol is still not well understood, likely due to its variable precursors, complex formation and atmospheric transformation processes mediated by meteorological conditions Petäjä et al, 2016;Tie et al, 2017;Xu et al, 2017). A number of studies have investigated the formation and aging processes of secondary aerosol (Takegawa et al, 2009;Huang et al, 2014Huang et al, , 2019Sun et al, 2014Sun et al, , 2016Wang et al, 2016;Duan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, the attenuation of incoming solar radiation caused by the ALW also decreases the photolysis rates, being unfavorable for photochemical activities and lowering the atmospheric oxidation capability (AOC). Field measurements show that a large fraction of SA in PM 2.5 has been observed in the NCP during wintertime (Sun et al, 2013;Guo et al, 2014;Xu et al, 2015). Therefore, decreased AOC generally does not facilitate the SA formation, particularly with regards to SOA and nitrate, to partially counteract the PM 2.5 enhancement caused by the ALW.…”
Section: Relationship Between Rh and Near-surface Pm 25 Concentrationsmentioning
confidence: 99%
“…Organic aerosol (OA) is a key component of PM 2.5 in ambient air, constituting of 20 %-90 % of the PM 2.5 mass concentration (Kanakidou et al, 2005;Zhang et al, 2007). Previous studies have confirmed a large mass fraction of OA in ambient PM 2.5 in various Chinese cities.…”
Section: Introductionmentioning
confidence: 99%